Novel modulatory effects of neurosteroids and benzodiazepines on excitatory and inhibitory neurons excitability: a multi-electrode array recording study - Puia, Giulia; GULLO, Francesca; Dossi, Elena; Lecchi, Marzia; Wanke, Enzo (Frontiers in Neural Circuits, 2012)
The balance between glutamate- and GABA-mediated neurotransmission in the brain is fundamental in the nervous system, but it is regulated by the ‘tonic’ release of a variety of endogenous factors. One such important group of molecules are the neurosteroids (NSs) which, similarly to benzodiazepines (BDZs), enhance GABAergic neurotransmission. The purpose of our work was to investigate, at in-vivo physiologically relevant concentrations, the effects of NSs and BDZs as GABA modulators on dissociated neocortical neuron networks grown in long-term culture. We used a multi-electrode array (MEA) recording technique and a novel analysis that was able to both identify the action potentials of engaged excitatory and inhibitory neurons and to detect drug-induced network up-states (burst). We found that the NSs tetrahydrodeoxycorticosterone (THDOC) and allopregnanolone (ALLO) applied at low nM concentrations, produced different modulatory effects on the two neuronal clusters. Conversely, at high concentrations (1 µM), both NSs, decreased excitatory and inhibitory neuron cluster excitability; however, even several hours after washout, the excitability of inhibitory neurons continued to be depressed, leading to a network long term depression (LTD). The BDZs clonazepam (CLZ) and midazolam (MDZ) also decreased the network excitability, but only MDZ caused LTD of inhibitory neuron cluster. To investigate the origin of the LTD after MDZ application, we tested finasteride (FIN), an inhibitor of endogenous NSs synthesis. FIN did not prevent the LTD induced by MDZ, but surprisingly induced it after application of CLZ. The significance and possible mechanisms underlying these LTD effects of NSs and BDZs are discussed. Taken together, our results not only demonstrate that ex-vivo networks show a sensitivity to NSs and BDZs comparable to that expressed in vivo, but also provide a new global in-vitro description that can help in understanding their activity in more complex systems.